(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the role and significance of foreign archaeological expeditions in the study of Paleolithic sites located in the territory of Uzbekistan. Particular attention is paid to the results of archaeological research conducted within the framework of international scientific cooperation, the application of modern research methods, and the achievements in studying the culture of the Paleolithic period. The study also highlights the scientific importance of research on the lifestyle of ancient humans in the territory of Uzbekistan, their tools, and cultural development. The contribution of foreign expeditions, including scholars from the United States, Japan, China, and Russia, who conducted archaeological excavations and scientific analyses, is examined, emphasizing their important role in the deeper study of the history of primitive society in Central Asia.